Changes of Learning Communication Models in New Normal Adaptation: From Classroom Learning to Distance Learning Environment - Joko S. Dwi Raharjo; Dony Hendartho; Endang Susanti; Retno Ekasari (Ilomata International Journal of Management, 2021)
Covid-19 pandemic has a significant impact on various aspects of life, both individually, organizationally and nationally. The decision of various countries in the world to do a "lockdown" in order to limit the transmission of the plague has an impact on continuity of economic wheels to education. Educational institutions began to close because of scarcity of students and difficulties in covering operational costs so that many teachers and management were laid off. For educational institutions that still survive must play a strategy to stay afloat and maintain their students able to learn, with the policy ‘Work from Home’ and ‘School from Home’. The pandemic to this day is not over yet and it is predicted that it will last long until the antivirus is found. However, in anticipation of bankruptcy, the government adopted adaptation of new habits (New Normal), habits that emphasize the implementation of health protocols in every activity. To carry out health protocols, educational institutions change the learning patterns from learning in classrooms to online learning. This has an impact on lecturers with demands to adapt quickly to existing changes. This study tries to analyze and examine the ability of lecturers to adapt learning communication models from classroom-based learning to online-based learning. With hope that this research will become a reference for the developed communication model and its application in adaptation of new habits (New Normal). The study was conducted by examining the results of previous study and in-depth interviews with lecturers to get a diverse picture so that generic conclusions can be drawn.